Rates of longitudinal change in 18F‐flortaucipir PET vary by brain region, cognitive impairment, and age in atypical Alzheimer's disease. Issue 6 (13th September 2021) - Phillips, Jeffrey S.; Nitchie, Frederick J.; Da Re, Fulvio; Olm, Christopher A.; Cook, Philip A.; McMillan, Corey T.; Irwin, David J.; Gee, James C.; Dubroff, Jacob G.; Grossman, Murray; Nasrallah, Ilya M.; ,
Abstract: Introduction: Longitudinal positron emission tomography (PET) studies of tau accumulation in Alzheimer's disease (AD) have noted reduced increases or frank decreases in tau signal. We investigated how such reductions related to analytical confounds and disease progression markers in atypical AD. Methods: We assessed regional and interindividual variation in longitudinal change on 18 F‐flortaucipir PET imaging in 24 amyloid beta (Aβ)+ patients with atypical, early‐onset amnestic or non‐amnestic AD plus 62 Aβ– and 132 Aβ+ Alzheimer's Disease Neuroimaging Initiative (ADNI) participants. Results: In atypical AD, 18 F‐flortaucipir uptake slowed or declined over time in areas with high baseline signal and older, more impaired individuals. ADNI participants had reduced longitudinal change in early Braak stage regions relative to late‐stage areas. Discussion: Results suggested radioligand uptake plateaus or declines in advanced neurodegeneration. Further research should investigate whether results generalize to other radioligands and whether they relate to changes of the radioligand binding site structure or accessibility.